2004
DOI: 10.3136/fstr.10.13
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical Analysis of the Injury of Spores by Reciprocal Pressurization

Abstract: Mechanical analysis of injury of spores of B. subtilis by quick decompression was investigated. The stress on the stress concentration point of germinated spores under 200, 300 and 400 MPa treatment was calculated to be 800 MPa, 1200 MPa and 1600 MPa, respectively, where this point was the highest point of stress concentration on the sporecoat. The stress showed values 4 times larger than treatment pressure. Sporecoat is a keratin-like scleroprotein. The tensile strengths of some polymers were 70 MPa (polyeste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…In this context, the idea of making HPP more “dynamic” in order to inactivate bacterial spores takes on a certain appeal. One such process has been the idea of “pulsed” or variable pressure processing; also referred to in the literature as reciprocal pressurization (RP) (Furukawa and others ; Furukawa and Hayakawa ), or repeated pressure treatment (Furukawa and others ). The idea was investigated by Hayakawa and others (), using a process of 600 MPa with a terminal temperature of 70 °C for 5 min, depressurizing to atmospheric pressure, and then repressurizing for 5 more cycles, and showed no survivors of Bacillus stearothermophilus .…”
Section: High‐pressure Processingmentioning
confidence: 99%
See 1 more Smart Citation
“…In this context, the idea of making HPP more “dynamic” in order to inactivate bacterial spores takes on a certain appeal. One such process has been the idea of “pulsed” or variable pressure processing; also referred to in the literature as reciprocal pressurization (RP) (Furukawa and others ; Furukawa and Hayakawa ), or repeated pressure treatment (Furukawa and others ). The idea was investigated by Hayakawa and others (), using a process of 600 MPa with a terminal temperature of 70 °C for 5 min, depressurizing to atmospheric pressure, and then repressurizing for 5 more cycles, and showed no survivors of Bacillus stearothermophilus .…”
Section: High‐pressure Processingmentioning
confidence: 99%
“…Both RP and CP treatments were more effective than heat alone, which resulted in little or no inactivation at the temperatures studied. Subsequently, Furukawa and Hayakawa () showed that just 1 decompression was sufficient to decrease the number of spore clumps by 50%. Since clumped spores were found to have 5 times greater heat resistance than single spores (Toda and Aiba ), the efficacy of RP was attributed to reduction in clumping during depressurization.…”
Section: High‐pressure Processingmentioning
confidence: 99%